KEMISKINAN DAN USAHA MIKRO, KECIL, DAN MENENGAH - N. Dwi Retnandari (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2009)
This paper would like to see the role of UMKM (Usaha Mikro, Kecil, dan Menengah//W/cro, Small and Middle Scale Unit) in tackling poverty. The main superiority of UMKM in tackling poverty is in its ability to create working spaces. UMKM usually developed in the villages and created a new center of economical growth without eliminating the primary sector (agriculture). The developing of UMKM has been impeded since the government failed to understand the nature of UMKM itself. In framing the policies related to the development of UMKM, the government has misassumption the nature of UMKM and the problems they faced. In fact in general the development of UMKM needs a more conducive environment. The step should be taken by the government in this case is to be more convenience ingiving the information to UMKM. There should be an effort to increase the demand of the product by UMKM.